PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL FLIPPED CLASSROOM DENGAN MEDIA INTERAKTIF DALAM PEMBELAJARAN TEMA 9 KELAS V SEKOLAH DASAR - Silvia Trisnawati; Aryo Andri Nugroho; Tri Sugiyono (Universitas Negeri Medan, 2021)
Abstract : This Classroom Action Research was motivated by the low learning outcomes of fifth grade students at SDN Pandeanlamper 02 on theme 8. The low class activities and the lack use of learning media chaused the decline of studenst’s motivation and enthusiasm during the learning process. The percentage of learning outcomes that have completed the KKM was 47% with average score of 66,65. This research aimed to improve student learning outcomes in learning theme 9 through the flipped classroom model with interactive media.The Classroom Action Research was carried out in three cycles. The subjects of this research were the fifth-grade students of SDN Pandeanlamper 02, totaling 34 students. The data in this research were obtained through observation, tests, and documentation. The results after doing research using the flipped classroom model with interactive media in the first cycle 47% completed the KKM with an average of 71,66, the second cycle increased 28% to 75% completing the KKM with an average of 77,08, and the third cycle increased 16% to 91% completing the KKM with an average of 84,89. So it can be concluded that the flipped classroom learning model with interactive media can increase student activity and learning outcomes in learning theme 9 for fifth grade in the second semester of SDN Pandeanlamper 02 Semarang. Keyword : learning outcomes, flipped classroom, interactive media Abstrak : Penelitian Tindakan Kelas ini dilatar belakangi oleh rendahnya hasil belajar peserta didik kelas V SDN Pandeanlamper 02 pada pembelajaran tema 8. Keaktifan peserta didik rendah. Kurangnya pemanfaatan media pembelajaran sehingga minat dan antusias peserta didik saat proses pembelajaran kurang. Prosentase hasil belajar yang tuntas KKM yaitu sebesar 47% dengan nilai rata-rata 66,65. Penelitian ini bertujuan untuk meningkatkan hasil belajar peserta didik pada pembelajaran tema 9 melalui model flipped classroom dengan media interaktif. Penelitian Tindakan Kelas ini, dilaksanakan selama tiga siklus. Subyek penelitian ini yaitu peserta didik kelas V SD Negeri Pandeanlamper 02 dengan jumlah 34 orang. Data dalam penelitian ini diperoleh melalui observasi, tes, dan dokumentasi. Hasil penelitian setelah dilakukan tindakan menggunakan model flipped classroom dengan media interaktif, hasil belajar peserta didik siklus I sebesar 47% tuntas KKM dengan rata-rata 71,66. Siklus II meningkat sebanyak 28% menjadi 75% tuntas KKM dengan rata-rata 77,08 dan siklus III meningkat 16% menjadi 91% tuntas KKM dengan rata-rata 84,89. Sehingga dapat disimpulkan bahwa model pembelajaran flipped classroom dengan media interaktif dapat meningkatkan keaktifan dan hasil belajar peserta didik pada pembelajaran tema 9 kelas V semester II SDN Pandeanlamper 02 semarang. Kata Kunci : Hasil Belajar, Flipped classroom, Media Interaktif